Hepatitis B virus nucleic acid amplification testing of Australian blood donors highlights the complexity of confirming occult hepatitis B virus infection. Issue 8 (20th March 2014) - Kiely, Philip; Margaritis, Angelo R.; Seed, Clive R.; Yang, Hung; Australian Red Cross Blood Service NAT Study Group
<x xml:space="preserve">Abstract</x> Background We present an analysis of the first 2 years of hepatitis B virus (HBV) nucleic acid testing (NAT) of the Australian donor population. Study Design and Methods Between July 5, 2010, and July 4, 2012, all blood donations were screened for HBV DNA and hepatitis B surface antigen (HBsAg). Donors who tested HBsAg negative but HBV NAT positive were assessed as occult hepatitis B infections (OBI) if reactive for antibodies to HBV core antigen (anti‐HBc). Donors who were anti‐HBc reactive but with nonrepeatable or nondiscriminated NAT results were assessed as HBV inconclusive pending follow‐up testing. Results During the study period a total of 2, 673, 521 donations were screened for HBV. Forty‐two chronic OBI infections (5.55/100, 000 donors) were identified compared to eight acute serologic window period infections (1.06/100, 000 donors). Of the 42 OBI cases, 23 (54.8%) were detected the first time they were screened for HBV DNA while 19 (45.2%) gave one or more HBV NAT–nonreactive results before detection. Of 68 donors initially assessed as HBV inconclusive and available for follow‐up, 10 later confirmed as OBI cases while 51 were NAT nonreactive but remained anti‐HBc reactive and OBI could not be excluded. Conclusion This study demonstrated a substantially higher prevalence of OBI compared to acute serologic window period HBV infections in Australian blood donors. Follow‐up testing of OBI cases indicates that HBV DNA is often only intermittently detectable in OBI, highlighting the importance of including anti‐HBc to optimize the HBV testing algorithm.